Neuron Culture Systems: Astrocyte‐Encapsulated Hydrogel Microfibers Enhance Neuronal Circuit Generation (Adv. Healthcare Mater. 5/2020). Issue 5 (4th March 2020) - Kim, Beom Jin; Choi, Ji Yu; Choi, Hyunwoo; Han, Sol; Seo, Jeongyeon; Kim, Jungnam; Joo, Sunghoon; Kim, Hyo Min; Oh, Chungik; Hong, Seungbum; Kim, Pilnam; Choi, Insung S.
Abstract : In article number 1901072 by Insung S. Choi and co‐workers, a 3D neuron‐culture system is fabricated by encapsulating astrocytes (green in the picture) in alginate microfibers and culturing hippocampal neurons (orange) on the aligned microfibers. The astrocyte‐laden microfibers enhance neurite outgrowth and synaptic formation as well as controlling the outgrowth directionality, suggesting a cytotherapeutic platform for neural injuries. The image was designed by co‐authors Sol Han and Hyunwoo Choi.